Diversity of arbuscular mycorrhizal fungi in the rhizosphere of Plantago coronopus in Northwestern Algerian coast - Souad Tabti; Fatima Zohra Bendimered-Mouri (Journal of Degraded and Mining Lands Management, 2022)
Mycorrhizal fungi play a major role in the functioning of ecosystems. However, their identification has remained a challenge for scientific research. This study presents the first identification report of species of arbuscular mycorrhizal fungi in the rhizosphere of the halophyte Plantago coronopus L. in Algeria. Samples of rhizospheric soil were collected in spring 2018 at three sites in the Bomo-plage dunes west of Oran, Algeria. The spores were isolated by wet sieving, morphologically identified, and quantified. The mean spore density was 107.94 spores 100 g-1 dry soil, which is high compared to other dune ecosystems. Endomycorrhizal spore morphotypes were involved in the following Genus: Glomus, Septoglomus, Rhizophagus, Diversispora, Funneliformis, Dentiscutata, Claroideoglomus, Scutellospora, and Entrophospora, to the following Family: Glomeraceae, Gigasporaceae, Diversisporaceae, Claroideoglomeraceae, and Acaulosporaceae. The Glomeraceae was the most dominant identified family. The identification of indigenous arbuscular mycorrhizal fungi has been shown to be essential for future programs to restore disturbed dune ecosystems.